The Comprehensive Systematic Review of Relationship of Intravitreal Steroid Implants to the Progression of Cataracts and Glaucoma - Arsya Firdaus; Setiawan Arif Wibowo (The International Journal of Medical Science and Health Research, 2025)
Introduction: Intravitreal steroid implants, such as dexamethasone (DEX) and fluocinolone acetonide (FAc), represent a significant advancement in managing chronic, vision-threatening conditions like diabetic macular edema (DME), retinal vein occlusion (RVO), and non-infectious uveitis. While their sustained-release mechanism offers prolonged therapeutic effect, concerns persist regarding their association with the progression of steroid-induced cataracts and glaucoma, which are common ocular complications of corticosteroid therapy (Kuppermann et al., 2007; Kempen et al., 2011). Methods: This systematic review screened and included studies based on stringent criteria: human studies of FDA-approved intravitreal steroid implants, with quantifiable outcomes on cataract and/or glaucoma progression, follow-up ≥6 months, and appropriate study designs (RCTs, cohort, case-control, systematic reviews). Data from 80 studies were extracted concerning implant type, patient characteristics, follow-up, cataract progression/surgery rates, intraocular pressure (IOP) elevation, glaucoma incidence, and association strength. Results: The evidence demonstrates a clear and significant association between intravitreal steroid implants and both cataract and glaucoma progression, with risk profiles varying markedly by implant type. Fluocinolone acetonide implants (Retisert, Iluvien) showed the highest risk, with cataract surgery required in 64.6% to 100% of phakic eyes and IOP elevation ≥10 mmHg in 65-79% of patients over extended follow-up (Callanan et al., 2008; Goldstein et al., 2007; Jaffe et al., 2005). Dexamethasone implants (Ozurdex) presented a lower but still elevated risk: cataract-related adverse events in 67.9% vs. 20.4% sham (Boyer et al., 2014), and IOP elevation rates of 11-41%, though rarely requiring surgical intervention (Maturi et al., 2016). Key risk factors included phakic status for cataract, and Black race, pre-existing glaucoma, and baseline uveitis activity for glaucoma (Friedman et al., 2013; Kempen et al., 2015). Discussion: The heterogeneity in outcomes is primarily explained by pharmacokinetics: FAc provides continuous release for 2.5-3 years, leading to cumulative toxicity, whereas DEX releases over 4-6 months, resulting in more transient effects. This necessitates a risk-stratified clinical approach, favoring DEX in phakic or glaucoma-prone patients, and considering FAc primarily in pseudophakic, low-glaucoma-risk patients requiring long-term control (Vieira et al., 2020; Liao et al., 2022). The long-term efficacy-safety balance, as seen in the MUST trial, indicates that while implants offer superior inflammation control, systemic therapy may yield better long-term visual acuity due to avoided ocular complications (Kempen et al., 2017). Conclusion: Intravitreal steroid implants are effective but carry a substantial, implant-dependent risk of cataract and glaucoma. Fluocinolone acetonide implants pose the highest risk, while dexamethasone implants offer a more favorable safety profile. Clinical management must involve careful patient selection, rigorous pre-treatment assessment of risk factors, and diligent, long-term monitoring for cataract progression and IOP elevation.